Critical Synthesis Package: Ambati Questionnaire on Knowledge and Attitudes Toward HIV/AIDS - Hugh Stoddard (Association of American Medical Colleges, 2013)
Abstract This This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to healthcare education of the Ambati Questionnaire on Knowledge and Attitudes toward HIV/AIDS (AQ), and (2) a copy of the AQ instrument developed by Balamurali Ambati, MD, PhD. The AQ is a self-report survey to measure knowledge and attitudes about AIDS patients and issues. The AQ consists of 48 selected response items. Six items measure knowledge of the signs and symptoms of the disease, 12 measure knowledge about transmission of HIV, and 30 measure attitudes towards HIV/AIDS patients. All items use a "yes," "no," or "I don't know" response scale with the "I don't know" responses excluded from scoring. There is no scoring guide or technical manual available. Little data on internal or test-retest reliability has been published and there has been no evidence produced to establish construct or external validity of the instrument. The norming sample was heterogeneous, so applications of the instrument to healthcare education are limited. Subsequent uses of the AQ have not significantly augmented the data or psychometric support for the instrument, and there is no reference to prior instruments or frameworks used in development. The AQ needs extensive work to establish validity evidence and it should be normed to a well-defined population before recommending its use in healthcare education. The lack of technical manual or a scoring guide severely inhibits further development of the instrument for use in scholarly inquiry.